Prevalence, drug resistance, and genotypic diversity of the RDRio subfamily of Mycobacterium tuberculosis in Ecuador: a retrospective analysis for years 2012–2016 - Castro-Rodriguez, Bernardo; Franco-Sotomayor, Greta; Benitez-Medina, Jose Manuel; Cardenas-Franco, Greta; Jiménez-Pizarro, Natalia; Cardenas-Franco, Camilo; Aguirre-Martinez, Juan Luis; Orlando, Solon Alberto; Hermoso de Mendoza, Javier; Garcia-Bereguiain, Miguel Angel (Frontiers in Public Health, 2024)
Introduction A major sublineage within the Mycobacterium tuberculosis (MTB) LAM family characterized by a new in-frame fusion gene Rv3346c/55c was discovered in Rio de Janeiro (Brazil) in 2007, called RDRio, associated to drug resistance. The few studies about prevalence of MTB RDRio strains in Latin America reported values ranging from 3% in Chile to 69.8% in Venezuela, although no information is available for countries like Ecuador. Methods A total of 814 MTB isolates from years 2012 to 2016 were screened by multiplex PCR for RDRio identification, followed by 24-loci MIRU-VNTR and spoligotyping. Results A total number of 17 MTB RDRio strains were identified, representing an overall prevalence of 2.09% among MTB strains in Ecuador. While 10.9% of the MTB isolates included in the study were multidrug resistance (MDR), 29.4% (5/17) of the RDRio strains were MDR. Discussion This is the first report of the prevalence of MTB RDRio in Ecuador, where a strong association with MDR was found, but also a very low prevalence compared to other countries in Latin America. It is important to improve molecular epidemiology tools as a part of MTB surveillance programs in Latin America to track the transmission of potentially dangerous MTB stains associated to MDR TB like MTB RDRio.